Synergy and Partnership in Algerian Agricultural Sector: Knowledge Management and Capitalization - Bernaoui, Radia; Hassoun, Mohamed (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
The objective of this study is to measure knowledge management of actors of agricultural sectors in Algeria through two major surveys. One for professionals to analyze their information practices and the other for researchers to understand their culture of knowledge sharing in order to offer a collaborative platform, tool of development for the actors of the agricultural sector. Indeed, the actors of agricultural sector demand this collaborative tool in order to manage, to transfer and to share knowledge. They want to create this community of sharing and collaboration between research and economic sector. The construction of an information system is a tool for development and transfer of research results to the destination sector of agricultural production. Because it is better for us to propose a model of information system capable of managing intellectual capital in the Algerian agricultural sector and generate value from intellectual assets. Then, the creation of a shared space should be considered in order to provide an accurate visibility of information and knowledge, to strengthen the institutions, setting up networks of actors. The point is to establish a synergy and a partnership between (scientists, professionals, political leaders…).